Phase behavior of lipid-based lyotropic liquid crystals in presence of colloidal nanoparticles - Venugopal, Edakkal; Bhat, Suresh K.; Vallooran, Jijo J.; Mezzenga, Raffaele (Langmuir, 2011)
We have investigated the microstructure and phase behavior of monoglyceride-based lyotropic liquid crystals in the presence of hydrophilic silica colloidal particles of size comparable to or slightly exceeding the repeat units of the different liquid crystalline phases. Using small angle X-ray scattering (SAXS) and differential scanning calorimetry (DSC), we compare the structural properties of the neat mesophases with those of the systems containing silica colloidal particles. It is found that the colloidal particles always macrophase separate in inverse bicontinuous cubic phases of gyroid (Ia3d) and double diamond (Pn3m) symmetries. SAXS data for the inverse columnar hexagonal phase (H(II)) and lamellar phase (L(alpha)) suggest that a low volume fraction of the nanoparticles can be accommodated within the mesophases, but that at concentrations above a given threshold, the particles do macrophase separate also in these systems. The behavior is interpreted in terms of the enthalpic and entropic interactions of the nanoparticles with the lamellar and hexagonal phases, and we propose that, in the low concentration limit, the nanoparticles are acting as point defects within the mesophases and, upon further increase in concentration, initiate nucleation of nanoparticles dusters, leading to a macroscopic phase separation.

Probing influence of mesophasic transformation on performance of self-emulsifying system: effect of ion - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (Molecular Pharmaceutics, 2012)
Self-emulsifying systems are mixtures of oils and surfactants, ideally isotropic, sometimes including cosolvents, which emulsify under conditions of gentle agitation, similar to those which would be encountered in the gastrointestinal tract. The process of self-emulsification has remained the center of attraction for most researchers. Controlled hydration of self-emulsifying systems shows formation of an intermediate gel phase which upon rupture forms an emulsion. Current work was undertaken to understand and explore the microstructural properties of intermediate gel phase which are believed to influence the performance (droplet size) of the final formulation. The effect of additives on microstructural properties of intermediate gel phase has also been investigated. Microstructural elucidation of hydrated samples of intermediate regimes was done by using techniques such as small angle X-ray scattering, differential scanning calorimetry and rheology. Samples from intermediate regimes showed formation of local lamellar structure which swelled with hydration. In the present work, the effect of addition of salt form of naproxen (sodium and potassium) and naproxen (base) on microstructural properties of intermediate regimes was investigated. Systems containing naproxen salts formed larger droplets whereas naproxen base formed smaller ones. Microstructural properties of intermediate lamellar structures were well correlated with performance of the final formulation. The current studies indicate that by controlling the properties of intermediate regimes optimized formulations with desired performance can be tailor-made.
Keywords: emulsion; lamellar structure; liquid crystal; Microstructure; Naproxen; self-emulsifying system